A Concise ReviewThe Ph Triggered Concept In Situ Ophthalmic Gel Of Sodium Cromoglycate, Diclofenac Sodium and Aceclofenac - Kurniawansyah, Insan Sunan; Farisa Desy Arya, Insi; Sopyan, Iyan (Universitas Padjadjaran (Unpad), 2024)
The ophthalmic solutions have a major problem that is the poor bioavailability, such as the attainment of optimal drug concentration at the site of action, which is compromised mainly due to precorneal loss resulting in only small fraction of the drug being ocularly absorbed. This is overcome by developing an in situ ophthalmic gel which increases the retention time of the drug. The present review describes the formulation and evaluation of in situ gel-forming ophthalmic drug delivery system of an anti allergy drug sodium cromoglycate, an anti-inflammatory drug diclofenac sodium and aceclofenac based on the pH triggered concept in situ gelation. All the formulations varies in concentration and the content used. Based on the results obtained, Sodium cromoglycate which has been formulated with gelrite and HPMC E15LV has the highest ocular residence time compared to the other two formulations.Keywords: Ophthalmic in situ gel,sodium cromoglycate, diclofenac sodium, aceclofenac, gelrite, HPMC E15LV